Analyzing the Lean Principles in Integrated Planning and Scheduling Methods - Sheikhkhoshkar, Moslem; El-Haouzi, Hind Bril; Aubry, Alexis; Hamzeh, Farook; Poshdar, Mani (International Group for Lean Construction, 2023)
The shortcomings and limitations of conventional planning and scheduling methods led to a great deal of emphasis on combining them and developing integrated scheduling methods. Also, lean principles and tools are included in the integrated scheduling methods' structure to develop more effective scheduling strategies. This paper implements a multi-step methodology to identify and analyze the lean principles utilized in integrated scheduling methods. The findings show that integrated scheduling methods, Building Information Modelling (BIM)-Last Planner System (LPS)-Kanban, BIM-LPS, Location-based Management System (LBMS)-LPS-CPM, and BIM-LBMS have included a variety of lean principles into their frameworks. Moreover, improving the reliability of the planning, increasing transparency, identifying and eliminating waste, detecting and solving spatiotemporal conflict, enabling the coordination of the look-ahead plans, and continuous flow of work have received the most attention in the integrated scheduling methods. This paper contributes significantly to the body of knowledge by raising project stakeholders' awareness of the lean principles utilized in integrated scheduling methods in construction projects.
Keywords: Lean principles; Integrated Scheduling Methods; SNA; Quantitative Analysis